(untitled) (Studia Prawnicze / The Legal Studies, 1980)
This article aims at presenting principal problems connected with the phenomenon of crimes of rape in Poland in the years 1970-1977. It presents data concerning the size and dynamics of this phenomenon in the light of statistical data gathered in result of instituting preparatory proceedings (by the Civic Milicia or procurator) as well as the data concerning the ways of closing cases conducted by the prosecuting organs. Further on, also on the basis of statistical data, the study presents the size and dynamics of convictions for rapes in the given period and discusses basic features characterizing population of persons convicted for these crimes. The analysis of the above statistical data allowed to reveal that certain changes in the dynamics and structure of the discussed phenomenon occured in comparison with the period before 1970. It must be pointed out first of all that beginning with 1975 a stagnation or ever recession of the number of crimes foreseen in article 168 of the criminal code may be observed. It should be mentioned further that a number of persons convicted for rapes commited in the towns has diminished and, simultanously, the number of persons convicted for such acts commited in the country has increased. Also, the age of persons convicted for rapes is constantly increasing. Special attention was brought in the article to the policy of punishing perpetrators of the crimes of rape. It was observed that this policy was aggravated in comparison with the period before 1970, especially beginning with 1973. This fact is closely connected with entering into force of the Supreme Court guiding principles for the judiciary of December 21, 1972 concerning the crimes of rape (article 168 of the criminal code) which recommended more severe repression of the perpetrators of such crimes. However, the process of aggravating the policy of punishing the persons convicted for rapes noted in 1973 does not seem to be a longlasting phenomenon. This is shown by the fact that already beginning with 1974 there seems to appear a gradual liberalization in this domain. This conserns especially the young audult convicts. More severe repression is still observed only in case of persons convicted on the basis of article 168 para 2 of the criminal code. It seems however, that this is first of all due to wider implementation by the judiciary of the rules contained in this article as far as the sanctions foreseen in it are concerned. The criminal code of 1932 binding untill 1970 did not distinguish a spearate, qualified crime of rape and - consequently - more severe sanctions for such acts. This was only introduced by the criminal code of 1969 now in force.